Investigating Italian parents' vaccine hesitancy: A cross-sectional survey - Francesco Napolitano; Alessia D'Alessandro; Italo Francesco Angelillo (Taylor & Francis Group, 2018)
This cross-sectional survey was designed to assess the prevalence of vaccine hesitancy and to identify factors associated among a randomly selected sample of parents. A questionnaire was self-administered from October to December 2017 to a sample of parents of children aged 2 to 6 years attending five randomly selected pre-schools in the geographic area of Naples, Italy. Out of the 727 selected parents, 437 returned the questionnaires for a response rate of 60.1%. The median of Parent Attitudes about Childhood Vaccines Survey (PACV) score among participants was 45.8 with a total of 141 parents (34.7%) scored a value ≥50 and were defined hesitant about the childhood vaccinations. Vaccine hesitancy was significantly more common among those who were concerned and among those were not sure that any one of the childhood shots might not be safe, among those who were concerned that their children might have a serious side effect from a shot, among those who were concerned that a shot might not prevent the disease, among those who delayed and refused at least a shot of vaccine for their children, and in those who are not sure and uncertain in the pediatrician. More than half of parents (53.8%) expressed a desire to receive additional information about the childhood vaccinations. Parents who were not sure and uncertain that to follow the recommended shot schedule is a good idea for their children and those who were parents of first-born children were more likely to need additional information. This study finds a high prevalence of vaccine hesitancy among parents suggesting that in the immunization program is necessary to achieve a higher quality of the relationship between pediatricians and the community.